The role of financial development and inclusion on economic development among the emerging market countries of Sub-Saharan African - Bakar, Hamad Omar
In recent decades, Sub-Saharan Africa (SSA) has achieved high growth with an average of 5.5% per annum, placing the region among the fast t growing in the world. Yet, this a hievement is neither robust nor sustainable due to various macroeconomic challenges facing the region including high unemployment and extreme poverty. Besides, most of the studie were conducted in advanced economies leaving SSA with limited literature regarding this link. Policy makers believ that, financial development and inclusion are powerful means towards sustainable economic development. This study aims to investigate the roleof financial developm nt and inclusion on economic development of SSA countries. The direct effects of financial d velopment and the growth enhancing transmission channels were examined in three (3) periods; the pre-Millennium Development Goal (pre-MD ) (1990-1999), during the MOGs (2000-2016), and the main period (1990-2016). The non-linear effect and financial inclusion was examined in a period of (1990-20 16) and (2007-2016) respectively. The study applied the System Generalized Method of Moment (SGMM) to estimate parameters in a system of equations when cross sections were more than time (N)T). The method involves regression both at level and at first difference into a system. The country-level sample data were collected from 45 SSA countries, from rs 1990 to 2016. The underlying theories were derived from economic growth (Harrod-Domar, Solow, and endogenou growth model) and financial (McKinnon-Shaw and Schumpeter) theories. The findings from direct effect of financial development on economic growth, representing preMDGs and MDGs periods have shown mixed results. However, the main period showed positive effect in all financial development indicators. Similarly, the direct effect of financial inclusion for all indicators showed positive effect. However, for the non-linear effect and growth enhancing transmission channels, the findings were mixed. For most cases, institutional quality, human capital and foreign direct investment are good growth enhancing transmission channels for the SSA region. The study identified financial development channels and non-linear effects on the economy. It also extended the scope of literature by using financial index as variable as well as provided new evidence on financial inclusion. In order to su tain its economic development, the SSA region has to widen the penetration of financial services especially provision of credit into productive sectors and accessibility offormal financial services to the rest of the society. As for non-linear effect, the results showed positive return albeit its challenges. Thus, to ensure inclusive economic development, the SSA region has to focus on institutional quality, human capital and FDI since they are the main growth transmission channels.